OP0176 S100a4 Regulates the Src-Thyrosine Kinase Dependent Differentiation of TH17 Cells in Rheumatoid Arthritis. (10th June 2014) - Brisslert, M.; Bian, L.; Svensson, M.; Santos, R.; Jonsson, I.-M.; Erlandsson, M.; Barsukov, I.; Andersson, K.; Carmo, A.; Bokarewa, M.
Abstract : Background: A calcium-binding protein S100A4 regulates non-muscle myosin assembly and activity and plays important part in cell motility and differentiation. The binding of S100A4 to calcium drives conformation changes and permits S100A4 to regulate the activity of its multiple intracellular protein partners placing S100A4 at the crossroad of several intracellular transduction mechanisms. In RA, S100A4 is abundantly expressed in synovial fibroblasts, macrophages and vascular endothelial cells of the inflamed joints and may be measured in synovial fluid and in blood. The clinical consequences of the high levels of S100A4 in RA patients are associated with resistant joint inflammation and high skeletal damage. Objectives: In the present study we evaluated the role of intracellular functions of S100A4 for T-cell responses in rheumatoid arthritis. Methods: A preclinical model of the methylated BSA induced arthritis was induced in S100A4-deficent mice lacking the entire S100A4 protein (S100A4KO) and in wild-type (WT) counterparts where the S100A4 gene was inhibited with a specific shRNA-lentiviral constructs (S100A4-shRNA). The subsets of Th-cell in synovial infiltrates were analysed by immunohistology and in spleens by flow cytometry and qPCR. Phosphorylation of STAT3 (pTy5705), CD5 (pTyr453), Fyn (pTyr530) and ZA70 (pTyr319/Syk, pTyr352) were analysed by flow cytometry in spleen cell cultures. Kinase activity of Fyn and Lck was analysed by phosphorylation of CD5 peptide. Results: Histological analysis of the inflamed joints demonstrated that S100A4-deficient mice had significantly alleviated joint inflammation and damage. Leukocyte infiltrates in the arthritic joints of S100A4-deficient mice presented accumulation of Foxp3 + Treg, while the effector T-cell population and the number of RORγt + and pSTAT3 + cells were reduced. T-cells of S100A4-deficient mice were characterized by a limited formation of Th17-cells, which was a result of low mRNA levels of RORγt and STAT3 (pTyr705) activity in spleen and low production of IL17 and IFNg. In vitro experiments provide evidence that S100A4 directly binds Lck and Fyn and reciprocally regulates their kinase activity towards TCR inhibitor CD5. Nuclear magnetic resonance analysis demonstrated an interaction between CD5 cytoplasmic domain and EF2-binding sites of S100A4. This suggests that S100A4 is able to disrupt intracellular interactions of CD5 and could modify its inhibition of TCR. Consequently, S100A4-deficiency was translated in low expression of CD5, and increased lymphocyte proliferation and phosphorylation of ZAP-70. Conclusions: Here we provide experimental evidence that S100A4 directly binds the Src-kinases Lck and Fyn and reciprocally regulates their kinase activity. S100A4-deficiency results in reduced activity of STAT3 suppressing transcription of RORgt and lineage differentiation of Th17-cells. The immunological events controlled by S100A4 are functionally important for the pathogenesis of arthritis, since the deficiency in S100A4 alleviates experimental arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5414